Interpersonal Skills of Madrasah Principals in Improving Teacher Performance - M Farid Yudha Bahari; Hanafiah; Faiz Karim Fatkhullah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research is motivated by the lack of managerial skills (interpersonal skills) of madrasah leaders which is one of the causes of their performance failure which has an impact on the educational institution they lead and has an impact on the weak performance of teachers. With the interpersonal skills of the madrasah principal, teachers and other staff are motivated to improve their performance. The purpose of this study was to find out about the interpersonal skills of madrasah principals in improving the performance of Islamic Religious Education teachers and the supporting and inhibiting factors of madrasah principals in communicating to improve teacher performance. The research method used qualitative research with a case study approach at Madrasah Aliyah Plus Al-Munir Sumedang. The results of the study concluded that the Principal of Madrasah Aliyah Plus Al-Munir has interpersonal skills which include communication skills, the ability to understand in interacting, and the ability to motivate in the very good category. The results of the study can be used as consideration for madrasah principals to further improve closer and more effective communication with teachers, better understand and listen to the needs and desires of teachers, and continue to encourage and motivate teachers to improve their performance.